Manajemen Perubahan dalam Peningkatan Kualitas Widyaiswara - Teguh Anggoro (JURNAL PENDIDIKAN DAN PELATIHAN PERTAHANAN, 2024)
This research departs from the problem of the low willingness of the Pusdiklat Bela Negara to change to improve its quality. Their performance demands are to produce students who have an understanding of defending the country and can actualize it and socialize it with others.  The argument built in this study is that the quality of widyaiswara in the state defense education and training center has not improved because there is no change in work culture. Thus, the proposition built in this study is, "Change management is a supporting factor in improving the quality/competence of widyaiswara". The formulation of this research problem is the effort of the State Defense Education and Training Center in improving the quality of widyaiswara? The purpose of this research is to describe and analyze the efforts made by the State Defense Education and Training Center to improve the quality of widyaiswara. The theory used in this study is the theory of change from Kurt Lewin in Chaerudin (2019: 75). Lewin described the change as occurring in 3 (three) stages, namely: unfreezing, moving, and refreezing. The research method used is qualitative descriptive. The data collection method is carried out through in-depth interviews, observations, documentation studies, and literature studies to collect supporting literature. The findings in this study are that leadership encouragement and organizational support are supporting factors in making changes. The conclusion of this research is to improve the quality of widyaiswara, carried out through change management, starting from the stages of unfreezing, moving, and refreezing, and this is a necessity for the existence of an organization to keep up with changes in its environment and the demands of the external environment